The formation of the art culture of the future primary school teachers by means of art as the necessary condition of their creative development in the context of professional competence - Лисевич, Олександра Вікторівна (Pedagogy of Higher and Secondary Education, 2019)
Lysevitch O. V. The formation of the art culture of the future primary school teachers by means of art as the necessary condition of their creative development in the context of professional competence. The article examines the problem of the formation of the art culture of the future primary school teachers, by means of art as the necessary condition of their creative development in the context of professional competence.The author states that it is necessary to create the circumstances which would stimulate the creative activity, and the creative atmosphere which is of great need for the formation of positive motivation and creative activity. The author also insists that the presence of creative personalities, creative process, and creative environment are the important factors for the realization of the pedagogical creativity in the process of teaching.